Translating the Words “Al -Qadr" in Surah Al Qadr: Examining Cultural and Linguistic Challenges in Quranic Translation - Alsbbagh, Yasir Ahmed; Abdullah, Imran Ho; Muthmainnah; Ali, Maysoon Kadhim (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
The enduring significance of Surah al-Qadr in contemporary discourse has prompted numerous translations from Arabic into English, sparking ongoing discussions around its interpretation. This study meticulously examines translations provided by seven prominent Quran translators, analyzing the methodologies employed in each rendition with a particular focus on the strategies used to translate the word 'Al-Qadr'. Employing a mixed-methods approach integrating quantitative and qualitative analyses, the study compares translations and scrutinizes procedures using Vinay and Darbelnet’s framework. Findings reveal varying degrees of success among translators; some achieve synonymous translations like Mohsin Khan’s “Night of Al-Qadr (Decree)” and Sahih International’s “Night of Decree,” while others provide interpretations such as Muhammad Sarwar’s “Night of Destiny” and Shakir’s “grand night” that may not fully capture the intended meaning. Assessment of accuracy to the original text suggests that translations like “Night of Decree” (Sahih International) and “Night of Power” (Yusuf Ali and Arberry) may be deemed more accurate due to their closer adherence to the specific terminology and intended meaning of "Al- Qadr" in the Quran. Factors contributing to the differences in translation include linguistic intricacies inherent in the Arabic term, cultural context, translation philosophy, target audience considerations, and individual expertise and understanding of Islamic theology and Arabic language among translators. This investigation offers valuable insights into Quranic language translation, enhancing understanding of the complexities involved and suggesting avenues for further research.